Manajemen Inovasi Untuk Revitalisasi Bahasa Sanskerta Dalam Mendukung Pendidikan Agama Hindu - Suparta, Ida Kade; Melianti, Desak Nyoman Vera; Utari, Ni Made Ayu Gumi; Yasa, I Nengah Sudana (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2025)
Sanskrit holds a highly significant role in Hindu society, particularly in religious practices. However, there is minimal attention given to the language, leading to considerable distortions in both the pronunciation and comprehension of mantras and sacred texts. This neglect also contributes to the loss of the ability to access Hindu teachings in their original form. The objective of this community service program is to revitalize the Sanskrit language, thereby increasing awareness among Hindus of its importance, strengthening the spiritual foundations of sacred texts, and positioning temples as centers for the preservation of Hindu traditions based on the Sanskrit language. This initiative adopts an innovation management approach by utilizing the potential of Pura Batu Bolong as a learning center. The program is implemented in four stages: planning, organizing, actuating, and controlling. One of the key outcomes of this program is the development of web-based Sanskrit learning media. Access to this learning resource is disseminated through educational posters installed in the Pura Batu Bolong area, which include links and QR codes. Based on survey results, this learning media has been deemed suitable for use in the revitalization of Sanskrit in support of Hindu religious education, with 71.5% of respondents indicating agreement and 14.3% expressing strong agreement.